Respuestas
Respuesta dada por:
66
m(n-x)-m(n-1)=m(mx-a)
![mn-mx-mn+m = m^{2}x -ma mn-mx-mn+m = m^{2}x -ma](https://tex.z-dn.net/?f=mn-mx-mn%2Bm+%3D++m%5E%7B2%7Dx+-ma)
![m+ma = x( m^{2} + m) m+ma = x( m^{2} + m)](https://tex.z-dn.net/?f=+m%2Bma++%3D+x%28+m%5E%7B2%7D+%2B+m%29)
![m(1+a) = x( m^{2} + m) m(1+a) = x( m^{2} + m)](https://tex.z-dn.net/?f=+m%281%2Ba%29+%3D+x%28+m%5E%7B2%7D+%2B+m%29)
![\frac{m(1+a)}{m(m+1)}= x \frac{m(1+a)}{m(m+1)}= x](https://tex.z-dn.net/?f=+%5Cfrac%7Bm%281%2Ba%29%7D%7Bm%28m%2B1%29%7D%3D+x+)
![\frac{1+a}{m+1}= x \frac{1+a}{m+1}= x](https://tex.z-dn.net/?f=+%5Cfrac%7B1%2Ba%7D%7Bm%2B1%7D%3D+x+)
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años